Secâvendî’ye Göre Kur’ân’daki Vakf-ı Lâzım Remizlerinde Vasl Yapmanın Anlama Etkisi - Hasan Bulut (Cumhuriyet İlahiyat Dergisi, 2023)
Every word of the Qur'an ensures the understanding of the divine will. The foundation signs in it were created for this purpose. Just like the punctuation marks that ensure the correct understanding of a Turkish sentence, the foundation marks in the Qur'an have assumed the same function. The signs of foundation, which give the opportunity to breathe by interrupting the recitation at the places where the mana is completed, and the signs of ibtida, which provides the recitation starting from the appropriate place for the integrity of the meaning, have a significant importance in the authentic interpretation of the Qur'an. The scholar, who wrote very important works related to the field and brought an independent topic under the name of "Secâvend" to the science of recitation, undoubtedly Muhammad b. Tayfur es-Secavendi. According to him, it is considered obligatory to dwell on the foundation denoted by the remzi (م) in the mushafs. Because when vasl is performed in these places, the nature and meaning of the verse changes. Based on these reasons, a foundation is different from other types of foundations. In this study, the signs of the need for foundation were examined within the framework of the verse integrity, and it was analyzed why Secavendi considered it necessary to make a foundation, taking into account the possible meanings that may occur in the case of vasl.